(untitled) (Canberra, 1994)
This book provides a sumary of a research program on the economics of Papua New Guinea's Tuna fisheries.
Keywords: Quản lý nghề cá,Fishery management,Fisherie; Economic aspects; Papua New Guinea,Papua New Guinea